O FENÔMENO DA CORRUPÇÃO E A SOCIEDADE DO CONHECIMENTO: DO CONHECIMENTO DAS CAUSAS À CONSTRUÇÃO DE BARREIRAS EFICAZES - Artur Parreira Goncalves (TRF2, 2018)
This article starts from the identification of the characteristics that define with some precision the concept of knowledge society and evaluates to what extent these characteristics will condition fundamental behaviors of society, particularly in the field of economics, social relations, education and politics. An important part of the thematic focus of the research is to identify characteristics favorable to the elimination of unethical behaviors in terms of interpersonal and social relations, and specifically the processes of corruption in economics and politics, which today are rife in many societies. The theoretical and practical concerns with the construction of future knowledge-based societies are now widely shared by researchers in the social sciences; and questions about the transparency of political, economic and social decisions are felt not only in scientific, religious, and cultural institutions, but they begin to trigger specific behavior in politics. This study is driven by these concerns and seeks to define the characteristics of knowledge societies, as well as identify resources that can control undesirable social behaviors such as corruption. The methodology used in the study combined two processes: data collection by questionnaire, submitted to an appropriate statistical treatment and the collection of opinions expressed by the interviewees on these subjects. Qualitative remarks made by respondents point out that disclosure should be made in the means to which most citizens have access and stress that even punishments imposed on proven acts of corruption must be disclosed in order to eliminate the feeling of impunity associated with such acts.